Comparative Analysis of Traditional Methods and Blockchain-Based Solutions of Real Estate Transactions - Holý, Tomáš; Jedlinský, Jakub; Bok, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis examines how real estate transactions are conducted in the Czech Republic and compares the traditional system with blockchain-supported land registry initiatives in Georgia and Sweden. It first maps the Czech legal and institutional framework, describes the roles of key actors, and illustrates the standard transaction process, including its costs and duration. The second part introduces blockchain technology and analyzes two foreign projects of land administration modernization: Georgia’s anchoring solution and Sweden’s smart contract pilot. A comparative analysis along four dimensions – legal and regulatory framework, system architecture, transaction process, and motivations for blockchain adoption – is then used to evaluate which elements could be transferred to the Czech context. Based on this analysis, the thesis proposes a conceptual model for a shared digital workflow platform in Czech real estate transactions. The findings suggest that potential benefits, such as shorter transaction times and better coordination among actors, stem primarily from process redesign and digitalisation rather than from blockchain itself. In the current Czech context, blockchain should therefore be considered an optional technical tool to be weighed against simpler, non-blockchain alternatives when designing future reforms to the real estate transaction system.
Vedoucí práce: Jakub Jedlinský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses